Arterial Calcium Stimulation with Hepatic Venous Sampling in the Localization Diagnosis of Endogenous Hyperinsulinism - Paloma Moreno-Moreno; María Rosa Alhambra-Expósito; Aura Dulcinea Herrera-Martínez; Rafel Palomares-Ortega; Luis Zurera-Tendero; Juan José Espejo Herrero; María Angeles Gálvez-Moreno (International Journal of Endocrinology)
Objective. The aim of this study was to assess the utility of arterial calcium stimulation with hepatic venous sampling (ASVS) in the localization diagnosis of endogenous hyperinsulinism. Patients and Methods. A retrospective descriptive study was performed including patients with endogenous hyperinsulinism who underwent ASVS. The histopathological diagnosis in patients who underwent a surgical procedure was used as the reference for the statistical study of the accuracy of this technique. Results. 30 patients were included with endogenous hyperinsulinism and nonconclusive imaging diagnosis was included. ASVS was performed in all cases. Surgery was performed in 20 cases. Insulinoma was removed in 19 patients; the location of all cases was detected in the ASVS. All cases of endogenous hyperinsulinism had a positive result for the ASVS, with this association being statistically significant (χ2=15.771; p<0.001). A good and statistically significant agreement was obtained between histopathologic diagnosis and ASVS results (K=0.518, p<0.001). Conclusions. ASVS is a useful procedure in the localization diagnosis of endogenous hyperinsulinism undetected by other imaging tests. This technique allows the localization of intrapancreatic insulinomas and represents useful tool for the diagnosis and surgical management of these tumors.